Analisis Pendidikan Islam dalam Puasa Ramadhan - Abd. Misno (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2020)
Perfection of Islam in various sharia rules has two values, namely thevalue of worship and the value of muamalah. Fasting is an attempt to distancethemselves from despicable acts and violates the provisions of Islamic teachings.Fasting is not only oriented toward physical acts of worship, but also acts ofspiritual worship that can save and prosper the people, both physically andspiritually, in this world and the hereafter. The study in this study uses the literaturemethod with descriptive analysis. Based on the results of the study regarding thevalue of Islamic education in Ramadan fasting, it was found that the value ofIslamic education in fasting consists of two things, namely honesty and patience